Customer Loyalty in the case of Business-to-Business Company: Will Marketing Mix Still Work? - Prasetya, Muhammad Azka; Maharani, Anita; Patiro, Shine Pintor Siolemba (Yayasan Ilomata, 2024)
Through this research, researchers highlighted the role of the marketing mix in influencing customer loyalty in business-to-business (B2B) companies. Researchers also highlighted the role of purchase decisions as a mediator between marketing mix and customer loyalty. From the conceptual perspective, marketing mix is generally considered more appropriate for B2C type companies, however, a number of studies show that marketing mix can also be applied as a marketing strategy for B2B but in a more complex context. In terms of methodology, this research approach is quantitative, and uses Partial Least Square analysis techniques. The analysis units involved are individuals who have been customers of B2B companies for at least 3 years and are spread across Jabodetabek. Due to limited B2B customers, the survey distribution technique was carried out using the snowball sampling method. The distribution of questionnaires was carried out for six months from September 2023-February 2024. The results obtained show that purchasing decisions cannot mediate between marketing mix and customer loyalty, however marketing mix can influence customer loyalty in B2B type companies. The managerial implication of the results of this research is that B2B companies can implement a marketing mix to encourage customer loyalty.